Comparison of Bupivacaine and Lidocaine Use for Postoperative Pain Control in Endodontics - Moradi, Saeed; Naghavi, Neda (Iranian Endodontic Journal, 2010)
INTRODUCTION: Many patients suffer from mild, moderate or severe pain during or after root canal therapy. Theoretically, post-operative pain control can be achieved by using long-acting local anesthetics. The aim of this study was to evaluate the efficacy of a long acting anesthesia, bupivacaine, on preventing post-operative pain associated with endodontic treatment, and to compare it with lidocaine. MATERIALS AND METHODS: This study was a double blind and randomized clinical trial on 30 patients' anterior maxillary teeth. The patients were divided into two groups of fifteen. One group was administered lidocanine (2% with 1:100000 epinephrine) local anesthesia and the other group was given bupivacaine (0.5% without epinephrine). The pain in patients were compared using the visual analogue scale (VAS) at definite times i.e. before treatment, during treatment and 2,4,6,8,10,12,24,36 and 48 hours after operation. Data were analyzed using One-way ANOVA tests. RESULTS: Bupivacaine significantly decreased postoperative pain compared to lidocaine. Postoperative pain was directly related to preoperative pain. Women reported more pain, though significant difference in postoperative pain report was not found between different ages. CONCLUSION: In conclusion, a single dose of bupivacaine 0.5% used in infiltration anesthesia could be more effective in reduction or prevention of post-operative endodontic pain compared with lidocaine.